OSL SENSITIVITY OF QUARTZ EXTRACTED FROM FIRED BRICKS FOR RETROSPECTIVE DOSIMETRY. Issue 9 (22nd August 2022) - Reimitz, Dan; Hupka, Ivan; Ekendahl, Daniela
Abstract: Optically stimulated luminescence of quartz extracted from fired materials has been used for retrospective dosimetry for about 40 years. Quartz sensitivity to thermoluminescence and optically stimulated luminescence can vary over few orders of magnitude. These discrepancies in sensitivity for the quartz originating from different parts of the world are still not yet fully understood. We have extracted quartz from bricks produced by three different companies in the Czech Republic. Quartz was extracted from fired bricks, as well as from the bricks before firing. Significant changes in quartz sensitivity were observed after firing process. Sensitivity can either increase or decrease, depending mainly on the maximum temperature achieved during firing process. For some samples, the sensitivity increased significantly after firing (7 times). Sensitivity also increased after repeated irradiation exposures. On the other hand, there were also samples for which the sensitivity did not increase after repeated cycles of irradiation.